Cre/lox-assisted non-invasive in vivo tracking of specific cell populations by positron emission tomography - Martin Thunemann (Nature Portfolio, 2017)
Non-invasive cell tracking is a powerful method to visualize cells in vivo under physiological and pathophysiological conditions. Here Thunemann et al. generate a mouse model for in vivo tracking and quantification of specific cell types by combining a PET reporter gene with Cre-dependent activation that can be exploited for any cell population for which a Cre mouse line is available.